Endoscopic Sinus Surgery vs. Traditional Techniques: Comparative Outcomes in Chronic Rhinosinusitis Management: Endoscopic Sinus Surgery vs. Traditional Techniques: Chronic Rhinosinusitis Management - Waheed, Abdul; Khatri, Vijay Kumar; Anwar, Zubair; Dogar, Muhammad Razzaq; Mahar, Ghulam Shabir; Mushtaq, Allah Bux; Naqvi, Ali Muntazir (Pakistan Journal of Health Sciences, 2024)
Chronic rhinosinusitis (CRS) is a common inflammatory condition of the paranasal sinuses, often resistant to medical therapy, necessitating surgical intervention. Endoscopic sinus surgery (ESS) is favored for its minimally invasive approach, yet comparison with traditional techniques remains clinically relevant. Objectives: To compare pre-operative findings and post-operative results between ESS and traditional sinus surgery in patients with CRS. Methods: This study included 140 CRS patients, equally assigned to ESS and traditional groups. Baseline evaluation comprised history, examination, and Lund–Mackay CT scores. Postoperative outcomes assessed were SNOT-22 scores, operative time, blood loss, hospital stay, and complications. Data were analyzed using t-tests for continuous variables and Chi-square tests for categorical variables, with p<0.05 considered significant. Results: Patients in the ESS group had shorter operative time (69 ± 12 vs. 91 ± 17 min; p<0.001), less blood loss (57 ± 11 vs. 118 ± 23 mL; p<0.001), and reduced hospital stay (1.3 ± 0.4 vs. 3.0 ± 1.0 days; p<0.001). SNOT-22 scores at 12 weeks also favored ESS (17.1 ± 6.4 vs. 25.5 ± 7.6; p=0.001). Total complication rate was lower in ESS (17.1% vs. 44.4%; p=0.001). Conclusions: ESS seems to give better outcomes, faster recovery, and fewer complications compared with traditional methods for CRS. It should be the preferred option whenever facilities and skills are available.